Monkeypox encephalitis with transverse myelitis in a female patient. Issue 3 (March 2023) - Cole, Joby; Choudry, Saher; Kular, Saminderjit; Payne, Thomas; Akili, Suha; Callaby, Helen; Gordon, N Claire; Ankcorn, Michael; Martin, Andrew; Hobson, Esther; Tunbridge, Anne J
Summary: The 2022 monkeypox outbreak has affected 110 countries worldwide, outside of classic endemic areas (ie, west Africa and central Africa). On July 23, 2022, the outbreak was classified by WHO as a public health emergency of international concern. Clinical presentation varies from mild to life-changing symptoms; neurological complications are relatively uncommon and there are few therapeutic interventions for monkeypox disease. In this Grand Round, we present a case of monkeypox with encephalitis complicated by transverse myelitis in a previously healthy woman aged 35 years who made an almost complete recovery from her neurological symptoms after treatment with tecovirimat, cidofovir, steroids, and plasma exchange. We describe neurological complications associated with orthopoxvirus infections and laboratory diagnosis, the radiological features in this case, and discuss treatment options.